Rhetorical Structure of Discussion Sections in Undergraduate Theses Written by students of the English Tadris study Program at IAIN Curup - Haryanti, Septri; Arsyad, Safnil; Sujarwati, Iis; Maisarah, Ira; Sofyan, Dedi (Universitas Bengkulu, 2025)
This qualitative study investigated the rhetorical structure of discussion sections in undergraduate theses, addressing a notable gap in research concerning specific institutional contexts and the need to examine the source of guidance and references utilized. The objectives of this study were to identify the rhetorical moves and steps employed by students, to explore how these patterns evolved across academic years (2020-2024), and to analyze the sources of guidance and references used. A corpus of 35 undergraduate theses from IAIN Curup's English Tadris study program was subjected to manual text analysis using the Loan & Pramoolsook (2015) framework. Further insights were gathered through semi-structured interviews with seven students who have graduated, with data analyzed using thematic analysis. The findings revealed that fundamental rhetorical moves, such as Move 2 (Reporting Results), were consistently obligatory. However, significant absence and trend to be optional were observed in higher-order analytical and evaluative moves, with crucial steps within Move 4 (Commenting on Results) often being optional, and Move 5 (Summarizing the Study), Move 6 (Evaluating the Study), and Move 7 (Deductions from the Study) rarely incorporated. Furthermore, the study identified that students primarily relied on previous theses and supervisor feedback for guidance. Formal institutional resources, such as the guideline book and academic writing classes, were underutilized. This suggests a need for more targeted pedagogical interventions to encourage advanced rhetorical competence in undergraduate thesis writing among students in the English Tadris study program at IAIN Curup. Keywords: Rhetorical Structure, Discussion Section, Undergraduate Thesis, Thesis Discussion Section, IAIN Curup